Prevalence and distribution of inactivity and weight excess in Spanish scholar children - Arturo Rodríguez-Hernández; Sebastián Feu Molina; Raúl Martínez-Santos; Ernesto de la Cruz-Sánchez (Federación Extremeña de Balonmano; University of Extremadura, 2011)
Abstract This work aims to study the distribution of leisure time physical activity pattern and weight status of Spanish schoolchildren. The sample corresponds to 6,803 school-aged children (3,491 boys and 3,312 girls), who took part in the Spanish National Health Survey 2006, being representative of the Spanish scholar population. It has assessed their pattern of physical activity and weight status through international body mass index cut offs. The relationship between the variables studied has been established through a multinomial logistic regression analysis. Physical inactivity is more prevalent in children that exceed a healthy weight, and there are regional differences in the distribution of a sedentary lifestyle and weight excess, as well as in different age groups and sex. Globally, 49.7% of Spanish schoolchildren have an unhealthy leisure time physical activity pattern, and 28.9% of them exceed the recommended weight for their age.